ECG screening in deaf children for long QT syndrome: are we following recommendations?. (29th September 2015) - Kang, SL; Jackson, C; Kelsall, W
Abstract : Background: Jervell and Lange Nielsen syndrome (JLNS) is characterised by congenital deafness and long QT syndrome. The prevalence of JLNS is up to 6 per million births.1 There are clear UK guidelines recommending ECG as a routine investigation in all children with severe to profound deafness to evaluate for long QT syndrome.2 Aims: This study aims to survey national practice of ECG screening in deaf children referred to cochlear implant centres (CIC) and review local practice. Methods: A questionnaire was sent to all paediatric CIC to establish whether ECG screening was routinely performed, who reviewed the ECG and to identify cases of long QT syndrome and any related deaths. Non respondents were followed up by telephone. A retrospective review was conducted for patients identified from the local CIC database. Results: Responses were obtained from all 19 paediatric CIC, 8 (42%) performed ECG screening in deaf children. ECGs were mostly read by ENT physicians and referred to cardiologists as necessary. Seven centres reported a total of 13 cases of long QT syndrome with two related deaths. In our local population, 187 children have undergone ECG investigations over 4 years. The ECGs were performed during sedation for MRI scanning. All ECGs are reported by a paediatrician with expertise in cardiology. In our cohort 14 (7.5%) children had abnormal ECGs of which two children were symptomatic. One definite case of long QT syndrome and 13 borderline cases were identified. There have been no deaths. Conclusion: Despite clear national guidelines for ECG screening in deaf children, there is a wide variation in practice. In one centre ECG screening was implemented following the deaths of two children. Our local practice of performing investigations including ECG and genetic blood tests at the same time as MRI sedation has been very successful. We would recommend that all ECGs are reviewed by experienced clinicians, as timely diagnosis of JLNS can be life saving.